2014
DOI: 10.1103/physrevb.89.075107
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth-limited control of orbital and magnetic orders in half-doped manganites by epitaxial strain

Abstract: The magnetotransport phase diagram of half-doped manganites Ln0.5A0.5MnO3 (Ln=La3+, Nd3+, etc., and A=Sr2+, Ca2+, etc.) is primarily dictated by the bare conduction bandwith (W0), which itself is controlled by the Mn-O-Mn bond angle, and the carrier concentration. In thin films, epitaxial strain (ε) provides an additional tool to tune W0 by selecting orbital ordering at fixed carrier concentration. Here, we will show that compressive or tensile epitaxial strain on half-doped manganites can have a tremendous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 20 publications
10
38
0
Order By: Relevance
“…Fine-tuning the growth conditions, in this case the laser frequency, triggers the subtle change of tetragonality required to produce one state or another. Similar dependencies of the saturation magnetization have been observed as a function of the substrate used in half-doped LCMO and LSMO 13 . Interestingly, coercivity follows the same evolution, presenting very low values (< 150 Oe) for low tetragonality and much higher ones above τ C , ranging between 400-600 Oe, which is the indication of a radical change in the magnetic state of the highly strained thin films, as shown later.…”
Section: X-ray Diffraction Shown Insupporting
confidence: 76%
“…Fine-tuning the growth conditions, in this case the laser frequency, triggers the subtle change of tetragonality required to produce one state or another. Similar dependencies of the saturation magnetization have been observed as a function of the substrate used in half-doped LCMO and LSMO 13 . Interestingly, coercivity follows the same evolution, presenting very low values (< 150 Oe) for low tetragonality and much higher ones above τ C , ranging between 400-600 Oe, which is the indication of a radical change in the magnetic state of the highly strained thin films, as shown later.…”
Section: X-ray Diffraction Shown Insupporting
confidence: 76%
“…2(b) shows variation of major peak, which is shifted to lower temperatures with magnetic field, although, the temperature of minor peak corresponding to T C is not changed. These results can be summarized for the successive magnetic phases with lowering of temperature, namely, PM from room temperature to charge ordered state which is in competition with FM phase and then finally converts into AFM insulator [27,28], as shown in Fig. 2(b).…”
Section: Resultsmentioning
confidence: 82%
“…By inducing a metal to insulator transition in the manganite, a modification in the tunnel barrier width could lead to a giant tunnel electroresistance [5], much larger than in conventional BaTiO 3 -based ferroelectric tunnel junctions [5,6,7] and even larger than in BaTiO 3 ferroelectric barriers with polarization dependent depletion layer in the semiconducting ferroelectric layer [8]. However, although such heterostructures have been fabricated yielding promising results [9], the actual properties and response of the ultrathin HD layer required for tunnel devices may differ from the known properties of nanometric layers [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the strain is not the only relevant factor, since the electronic bandwidth seems to play a key role. For instance, Gutiérrez et al [10] recently showed, by means of an exhaustive study of the transport and magnetic properties of La 0.5 Sr 0.5 MnO 3 (LSMO) and La 0.5 Ca 0.5 MnO 3 (LCMO) thin films, that the magnetization and metallic behaviour of LSMO films can be largely controlled by strain, while LCMO films remain in a non-FM insulating state independently of the applied strain. The narrower bandwidth of LCMO seems to play a relevant role, by promoting electron localization and favouring the appearance of electronic phase separation and charge localization as already observed in bulk HD manganites [15].…”
Section: Introductionmentioning
confidence: 99%